A report on the practice in industry training in fish preservation. - Mariano, Dolores S. (College of Fisheries, University of the Philippines, 1958)
Fish is next to rice as the most important subsistence among Filipinos. Therefore it merits as such attention to more than any other subsistence as meat, corn or bread. At present, we do not produce enough fish to meet the demand of the public. This is clearly shown by the importation of this item from other countries in form of canned goods. For this reason, the government is now paying more attention to the development of fishing industry. As matter of fact, different fishery schools are now being established in other islands where fish are abundant. Laws have been promulgated to regulate the exploitation and utilization of our fish resources.